Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats. (1st February 2023) - Shi, Ting; Xu, Lin-Lin; Chen, Liang; He, Jun; Wang, Ye-Ke; Chen, Feng; Chen, Yang; Giesy, John P.; Wang, Yu-Ting; Wu, Qian-Hui; Xu, Wen-Li; Chen, Jun; et al.
Abstract: Microcystins (MCs) produced by some cyanobacteria can cause toxicity in animals and humans. In recent years, growing evidence suggests that MCs can act as endocrine disruptors. This research systematically investigated effects of microcystin-LR (MC-LR) on endocrine organs, biosynthesis of hormones and positive/negative feedback of the endocrine system in rats. Male, Sprague-Dawley rats were acutely administrated MC-LR by a single intraperitoneal injection at doses of 45, 67.5 or 90 μg MC-LR/kg body mass (bm), and then euthanized 24 h after exposure. In exposed rats, histological damage of hypothalamus, pituitary, adrenal, testis and thyroid were observed. Serum concentrations of corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH) and corticosterone (CORT), expressions of genes and proteins for biosynthesis of hormones were lesser, which indicated an overall suppression of the hypothalamus-pituitary-adrenal (HPA) axis. Along the hypothalamus-pituitary-gonadal (HPG) axis, lesser concentrations of gonadotropin-releasing hormone (GnRH) and testosterone (T), but greater concentrations of luteinizing hormone (LH), follicle-stimulating hormone (FSH) and estradiol (E2) were observed. Except for greater transcription of cyp19a1 in testes, transcriptions of genes and proteins for T and E2 biosynthesis along the HPG axis were lesser. As for the hypothalamus-pituitary-thyroid (HPT) axis, after MCs treatment, greater concentrations of thyroid-stimulating hormone (TSH), but lesser concentrations of free tri-iodothyronine (fT3) were observed in serum. Concentrations of free tetra-iodothyronine (fT4) were greater in rats dosed with 45 μg MCs/kg, bm, but lesser in rats dosed with 67.5 or 90 μg MCs/kg, bm. Transcripts of genes for biosynthesis of hormones and receptors along the HPT axis and expressions of proteins for biosynthesis of tetra-iodothyronine (T4) and tri-iodothyronine (T3) in thyroid were significantly altered. Cross-talk among the HPA, HPG and HPT axes probably occurred. It was concluded that MCs caused an imbalance of positive and negative feedback of hormonal regulatory axes, blocked biosynthesis of key hormones and exhibited endocrine-disrupting effects. Graphical abstract: Image 1 Highlights: Microcystins caused pathological injury of hypothalamus, pituitary, adrenal, testis and thyroid. Microcystins affected concentrations of hormones in blood serum. Microcystins altered transcription of genes and expression of proteins for hormones biosynthesis. Microcystins disrupted positive and negative feedback of hormonal regulatory axes. Effects of microcystins on interactions among endocrine axes probably occurred.